Methylobacterium extorquens RSH Enzyme Synthesizes (p)ppGpp and pppApp in vitro and in vivo, and Leads to Discovery of pppApp Synthesis in Escherichia coli - Sobala, Michał; Bruhn-Olszewska, Bożena; Cashel, Michael; Potrykus, Katarzyna (Frontiers in Microbiology, 2019)
In bacteria, the so-called stringent response is responsible for adaptation to changing environmental conditions. This response is mediated by guanosine derivatives [(p)ppGpp], synthesized by either large mono-functional RelA or bi-functional SpoT (synthesis and hydrolysis) enzymes in β- and γ-proteobacteria, such as Escherichia coli. In Firmicutes and α-, δ- and ε-proteobacteria, large bifunctional Rel-SpoT-Homologs (RSH), often accompanied by small (p)ppGpp synthetases and/or hydrolases devoid of regulatory domains, are responsible for (p)ppGpp turnover. Here, we report on surprising in vitro and in vivo properties of an RSH enzyme from Methylobacterium extorquens (RSHMex). We find that this enzyme possesses some unique features, e.g. it requires cobalt cations for the most efficient (p)ppGpp synthesis, in contrast to all other known specific (p)ppGpp synthetases that require Mg2+. In addition, it can synthesize pppApp, which has not been demonstrated in vitro for any Rel/SpoT/RSH enzyme so far. In vivo, our studies also show that RSHMex is active in E. coli cells, as it can complement E.coli ppGpp0 growth defects and affects rrnB P1-lacZ fusion activity in a way expected for an RSH enzyme. These studies also led us to discover pppApp synthesis in wild type E.coli cells (not carrying the RSHMex enzyme), which to our knowledge has not been demonstrated ever before. In the light of our recent discovery that pppApp directly regulates E. coli RNAP transcription in vitro in a manner opposite to (p)ppGpp, this leads to a possibility that pppApp is a new member of the nucleotide second-messenger family that is widely present in bacterial species.